Using magneto-electroluminescence as a fingerprint to identify the spin polarization and spin–orbit coupling of magnetic nanoparticle doped polymer light emitting diodes. Issue 28 (21st May 2019) - Jia, Weiyao; Ikoma, Tadaaki; Chen, Lixiang; Zhu, Hongqiang; Tang, Xiantong; Qu, Fenlan; Xiong, Zuhong
Abstract : The existence of spin polarization was confirmed while spin–orbit coupling was ruled out in Fe3 O4 -based PLEDs by magneto-electroluminescence analysis. Abstract : The spin polarization and spin–orbit coupling (SOC) in polymer light emitting diodes (PLEDs) with the active layer doped with Fe3 O4 nanoparticles (NPs) were identified through magneto-electroluminescence (MEL). By comparing the MEL characteristics such as linewidth and magnitude between PLEDs with and without Fe3 O4 dopant, we confirmed the existence of spin polarization, but ruled out the existence of SOC. Although the spin polarization is positive to electroluminescence, the brightness–current characteristics suggested that the current efficiency of the doped PLED does not improve. We attributed it to the current leakage caused by the Fe3 O4 NPs in the active layer. This work is beneficial for us to further understand the effect of magnetic nanoparticle doping on the dynamic behavior of excitons and polaron pairs in organic semiconductor devices.